Dynamics of Retail Methamphetamine Markets in New York City, 2007-2009 - Wendel, Travis ([Verlag nicht ermittelbar], 2014)
The study was conducted to provide information about markets for, distribution of, and use of methamphetamine in New York City, both inside and outside of the MSM (men who have sex with men)/gay community. The study used Respondent Driven Sampling to recruit 132 methamphetamine market participants. Each respondent participated in a one to two hour structured interview combining both qualitative and quantitative responses. Each respondent was invited to recruit three additional eligible participants. Data collected included demographics, social network data, the respondent's market participation in obtaining and providing methamphetamine, consumption of methamphetamine, and experience with the criminal justice system and crime associated with participation in methamphetamine markets.